Growth And Physical Characterization Of Native Oxide Thin Film On N-Type Gallium Nitride Substrate By Ti-Iermal Oxidation In Nitrous Oxide Ambient - Oon, Hooi Shy (2013)
Thermal oxidation of n-type GaN substrate in nitrous oxide (N20) ambient has been systematically investigated. The thermal oxidation process was performed in a horizontal quartz tube furnace under N20 ambient with now rate of 150 mL/min. The effects of oxidation times (30 - 120 min) and oxidation temperatures (700 - 1000C) on the thermal oxide grown on GaN were studied. Physical properties of the samples were then examined. Fourier Transform infrared spectrometer, X-ray diffraction and X-ray photoelectron spectroscopy were employed to identify the oxide layer formed on top of the GaN. Based on the analysis, Ga203 and GaON compounds were formed when thermally oxidized GaN at 700 to 900°C. However, for GaN thermally oxidized at 1000°C, non-stoichiometry Ga.O, and/or GaxOyNz compounds were formed. Apart from that, field-emission scanning electron microscope and atomic force microscope results revealed some distinct change on surface of all oxidized samples. The surface roughness of the oxide layer was also found to be increased with both the oxidation times and temperatures.